Homozygous DNAH1 frameshift mutation causes multiple morphological anomalies of the sperm flagella in Chinese. Issue 2 (24th November 2016) - Wang, X.; Jin, H.; Han, F.; Cui, Y.; Chen, J.; Yang, C.; Zhu, P.; Wang, W.; Jiao, G.; Wang, W.; Hao, C.; Gao, Z.
Abstract : This study aimed to investigate the genetic pathogeny of multiple morphological anomalies of the flagella (MMAF), which is a genetically heterogeneous disorder leading to male infertility. Nine patients with severe asthenozoospermia caused by MMAF were recruited. Whole genome sequencing and Sanger sequencing were performed, and we found that four of the nine patients were affected by the same homozygous frameshift mutation c.11726_11727delCT (p.[Pro3909ArgfsTer33]) in exon 73 of dynein axonemal heavy chain 1 ( DNAH1 ) gene. The parents and the sibling of proband 1 were all identified as heterozygous carriers. This mutation was distinct from previously reported DNAH1 mutations associated with MMAF and only affected the East Asian group. Furthermore, the variant DNAH1 protein could not be detected in spermatozoa by Western blot or immunofluorescence staining although DNAH1 mRNA was expressed in the spermatozoa. Scanning electron microscopy and transmission electron microscopy analysis showed the anomalies in sperm flagella morphology and ultrastructure in patients carrying this genetic variant. In conclusion, our results add to knowledge of the genetic pathogeny of MMAF and further confirmed the effectiveness of genetic screening in the diagnosis of MMAF. Abstract :